The overwintering situation and influencing factors of Fulmekiola serrata in Yunnan sugarcane planting areas of China - Jiong Yin; Ya-Lian Gao; Zhi-Xing Lu; Zhi-Ming Luo; Yin-Hu Li; Chang-Mi Wang; You-Qing Chen (Scientific Reports)
Abstract Sugarcane thrips, Fulmekiola serrata (Kobus), is a common leaf pest of sugarcane. To clarify the occurrence and overwintering of F. serrata in Yunnan sugarcane planting areas of China in winter and the influencing factors, five surveys on the occurrence and overwintering of thrips in sugarcane were carried out at three bases of the Sugarcane Research Institute, Yunnan Academy of Agricultural Sciences, in January and February 2023, targeting five varieties and two sugarcane growth periods. The results showed that the average number of adults was 2.86 individuals/plant, significantly greater than that of nymphs, at 0.07 individuals/plant. The average number of females was 1.87 individuals/plant, significantly greater than that of males, at 0.06 individuals/plant. Except for the first survey, the average number of thrips of Yunzhe 081,608 was the highest in the other four surveys, but Guiliu 05,136 was the lowest in the five surveys. The average number of thrips at the seedling stage was 2.86 individuals/plant, significantly greater than that at the mature stage, at 0.98 individuals/plant. The average numbers of adults were 2.48 and 2.12 individuals/plant at the Mabao and Sugarcane Institute bases, respectively, significantly greater than that at the Lengshuigou base, at 1.16 individuals/plant. In conclusion, F. serrata mainly overwintered as adults in the heart leaves of sugarcane at the seedling stage, with females in the majority, and the sugarcane growth period had the greatest influence on the average number of thrips. As the planting area of autumn-planted sugarcane and winter-planted sugarcane increases annually, clarifying the occurrence and overwintering of thrips in winter can provide a foundation for monitoring and effectively managing of F. serrata.